Care, maternal welfare, and women's associations in French colonial Africa: The Œuvre du Berceau indigène in Togo and Cameroon (1922-1935) - (:unkn) unknown (My University, 2024)
After the First World War, the demographic decline of the African colonies became a significant concern for France and its empire. The colonizers feared that the workforce needed to develop colonized territories would not be sufficiently renewed in the future due to the influence of “social diseases” such as venereal diseases and alcoholism. To combat these threats, colonial health services invested in maternal and child health. Pregnant women, newborn babies, and young children became the prime targets of a health policy designed to promote population growth and secure the future of the colonial empire. As former German colonies occupied by France and Great Britain during the conflict, Togo and Cameroon were particular colonial contexts redrawn by the history of the First World War. They were part of the territories entrusted under mandate to the victors by the League of Nations in 1922. In this context, the promotion of maternal and child protection initiatives was central to French propaganda during the inter-war period. In this article, I trace the history of two twin charity associations: the Œuvre du Berceau Indigène in Togo (created in 1924) and Cameroon (1932).The aim is to study the highly unusual birth of these associations and to place them in thecontext of the general development of maternal and child health care in these territories. I arguethat these associations played a crucial role in promoting French inter-war colonialism butwere also a means of personal advancement for Auguste Bonnecarrère, successively Governorof Togo (1924-1931) and Cameroon (1932-1934). This paper shows how these associationsbecame central to the communication of French colonial action in the mandated territoriesand examines the very nature of the Œuvre du Berceau, which were presented as women’sassociations but lay under the control of Mr and Mrs Bonnecarrère.
Keywords: African Research